2020
DOI: 10.1038/s41386-020-0669-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of dopamine in dynamic effort-reward integration

Abstract: When deciding to act, the neurotransmitter dopamine is implicated in a valuation of prospective effort and reward. However, its role in dynamic effort-reward integration during action, a process central to everyday behaviour, remains unclear. In a placebocontrolled, within-subject, study, we probed the impact of increasing brain dopamine levels (150 mg of levodopa) and blocking dopamine receptors (1.5 mg of haloperidol) in the context of a novel dynamic effort task in healthy human subjects. We show that modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 35 publications
8
21
0
Order By: Relevance
“…Although preference for the sweetened solution is typically thought to reflect anhedonia, the inflammatory effects on motivation appear to relate to reduced effort expenditure, rather than deficits in reward processing (Chudasama et al, 2003 ; Paine et al, 2011 ; Asinof and Paine, 2014 ). Effort expenditure is in part governed by the mPFC which integrates motivational, reward, and cognitive information (van Heesch et al, 2014 ; Yeh et al, 2015 ), with reduced motivation associated with mPFC dysfunction (Felger and Treadway, 2017 ; Michely et al, 2020 ). Such a process could drive the increase in omission rate noted here in the mTBI:LPS animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although preference for the sweetened solution is typically thought to reflect anhedonia, the inflammatory effects on motivation appear to relate to reduced effort expenditure, rather than deficits in reward processing (Chudasama et al, 2003 ; Paine et al, 2011 ; Asinof and Paine, 2014 ). Effort expenditure is in part governed by the mPFC which integrates motivational, reward, and cognitive information (van Heesch et al, 2014 ; Yeh et al, 2015 ), with reduced motivation associated with mPFC dysfunction (Felger and Treadway, 2017 ; Michely et al, 2020 ). Such a process could drive the increase in omission rate noted here in the mTBI:LPS animals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cytokines can potentially affect multiple aspects of dopamine function, leading to decreased synthesis, impaired packaging and release, increased reuptake, or decreased dopamine receptors (Felger and Treadway, 2017 ), providing a potential mechanistic explanation for the ability of LPS treatment to reduce impulsivity. Reduced dopamine is also associated with lower effort-based expenditure (Michely et al, 2020 ) and may thus also account for the decreased motivation seen post-LPS in injured animals. Future work is needed to evaluate the specific effects of acute inflammatory insults on dopaminergic neurotransmission and whether the effects are transient or more long-lasting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pharmalogical enhancement of dopamine transmission increases the willingness of animals to accept delays and to expend effort to obtain rewards (for a review, see Webber, Lopez-Gamundi, Stamatovich, de Wit, & Wardle, 2020). Two studies with human subjects also reported higher force production in states with augmented dopamine transmission (Chong et al, 2015;Le Bouc et al, 2016;Michely et al, 2020). Further, augmented dopamine transmission increased response vigour (reduced reaction times) in a temporal discounting and reinforcement learning task (Rihet, Possamaï, Micallef-Roll, Blin, & Hasbroucq, 2002;Westbrook et al, 2020;Wagner et al, 2020).…”
Section: Dopamine and Response Vigourmentioning
confidence: 99%
“…The integration of reward and effort involves dopaminergic computations (see, e.g. Michely et al, 2020). Congruously, effort-based decision making appears to be disrupted in conditions related to dopaminergic function, such as major depressive disorder and Parkinson's disease (Le Bouc et al, 2016;Yi et al, 2010), underlining the relevance of measuring response vigour during value-based decision making.…”
Section: Relevancementioning
confidence: 99%
See 1 more Smart Citation